1999
DOI: 10.1108/10662249910297778
|View full text |Cite
|
Sign up to set email alerts
|

Security implications of electronic commerce: a survey of consumers and businesses

Abstract: Electronic commerce is poised to become one of the major applications areas in the Internet / World Wide Web environment, with significant growth forecast to occur within the next two to three years. However, one of the significant requirements for the success of e-commerce is trust, on the part of both the consumers and businesses offering services. It can be observed that while e-commerce services are now being offered on the Internet, a number of examples can be cited that suggest sufficient protection has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(138 citation statements)
references
References 4 publications
7
123
0
8
Order By: Relevance
“…However, in order to identify the primary inhibitors to the development of e-commerce in Syria, we have identified the barriers according to their importance and presented in Table 7. Nonetheless, in terms of the significance of the different inhibitors, our findings were in line with the results of previous related studies (Jarvenpaa & Todd, 1996-1997Furnell & Karweni, 1999;Hoffman et al, 1999;Mukti, 2000;Fenech & O"Cass, 2001;Udo, 2001) in the sense that online security was perceived as the single most important barrier. But interestingly, the lack of available online payment methods barrier was ranked second in terms of significance as a major impediment to embracing Internet commerce in Syria.…”
supporting
confidence: 82%
“…However, in order to identify the primary inhibitors to the development of e-commerce in Syria, we have identified the barriers according to their importance and presented in Table 7. Nonetheless, in terms of the significance of the different inhibitors, our findings were in line with the results of previous related studies (Jarvenpaa & Todd, 1996-1997Furnell & Karweni, 1999;Hoffman et al, 1999;Mukti, 2000;Fenech & O"Cass, 2001;Udo, 2001) in the sense that online security was perceived as the single most important barrier. But interestingly, the lack of available online payment methods barrier was ranked second in terms of significance as a major impediment to embracing Internet commerce in Syria.…”
supporting
confidence: 82%
“…Also, the inherent security risk of a mobile office based on wireless technology, for which the airwaves are open to intruders, threatens users as well (Karygiannis and Owens, 2002). Previous studies have found a negative impact of security risk on users' value, especially when dealing with sensitive tasks such as online banking (Furnell and Karweni, 1999;Lee, 2009). Thus, in a mobile office that is used to handle sensitive corporate data, security risk may be big burden to users, thereby influencing their perceived value in a negative way.…”
Section: H5d: Time Risk Will Negatively Affect Perceived Value Of Mobmentioning
confidence: 99%
“…According to (Furnell and Karweni, 1999), although these advances have reduced the possibility of security breaches, customers do not adequately understand these security controls and the associated complex terminologies (Suh and Han, 2003). Moreover, it is not necessary (and also highly unlikely) that customers are aware of which technologies are implemented in risky technologies they use (Suh and Han, 2003).…”
Section: Perceived Controlmentioning
confidence: 99%
“…A number of studies (e.g., Aldridge, et al, 1997;Bhimani, 1996;Furnell and Karweni, 1999;Gefen, 2000;Ratnasingham, 1998) have discussed the basic securitycontrol requirements in risky technologies which may be divided into five categories, namely: authentication (communicating or transacting parties are who they claim to be), non-repudiation (neither of the party should be able to deny having participated in a transaction after the fact), confidentiality (warrants all communication between trading parties to be restricted to parties involved in transaction), privacy protection (ensures that personal information about customers collected from their electronic transactions is protected from disclosure without permission) and data integrity (data under transmission is not created, intercepted, modified or deleted illicitly). These requirements are accomplished by various technologies, such as encryption, third-party certificates, digital signatures, and compliance with privacy policy (Aldridge, et al, 1997;Garfield and McKeown, 1997;Ratnasingham, 1998).…”
Section: Perceived Controlmentioning
confidence: 99%